The Kepuasan Mahasiswa Universitas Bumigora Terhadap Pelayanan E-Commerce - Ramdani, Rizal; Alpiansah, Restu; Komala, Rina; Mulawarman, Logi (Universitas Bumigora, 2023)
The use of e-commerce is growing rapidly now days. By the increasing development of e-commerce in Indonesia, customers are being influenced to find service quality to achieve customer satisfaction. This study investigated the relationship between service quality and customer satisfaction among Bumigora University students on the Shopee platform. A total of 120 samples were used in this study. According to this study's findings, all the service quality variables have a positive and significant influence. Further, this study discovered that website design has the biggest impact on customer satisfaction. This study also offers for establishing and increasing service quality to maintain customer satisfaction. In addition, e-commerce practitioners should be concerned with improving service quality surrounding students